SLA as an interdiscipline: A bibliometric study - Chen, Meng-Lin (Studies in Second Language Learning and Teaching, 2023)
Nowadays, research in second language acquisition (SLA) is becoming increasingly interdisciplinary while many technical frontiers and research hotspots have emerged. Many studies focus on interdisciplinary topics, but few in-depth studies have been conducted on interdisciplinarity. This study examined the interdisciplinarity of SLA and the interdisciplinary development process using a bibliometrics approach. The study has found that the SLA discipline has played roles as both the provider and recipient of knowledge in the development of interdisciplines. In the first case, SLA theories and methods flow into the research areas of life sciences and technology to form interdisciplinary studies with brain research, neurology, cognition, computer technology, and engineering, making SLA a provider of knowledge In the second case, SLA research receives knowledge from areas of arts and humanities and social sciences as well as from interdisciplinary studies within its own discipline, making SLA a receiver of knowledge. The new insights into the interdisciplinarity of SLA provided in this study are helpful for our deeper understanding of the interdisciplinary nature of the SLA discipline.